KORELASI ANTARA MINAT DENGAN PRESTASI BELAJAR PADA PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN SISWA KELAS X MIPA 2 SEKOLAH MENENGAH ATAS NEGERI 1 SEPAUK TAHUN PELAJARAN 2021/2022 - Hartini, Agnesia; Mardawani, Mardawani; Tinum, Tinum (STKIP Persada Khatulistiwa Sintang, 2022)
The purpose of this study wa to determine the correlation between interest and learning achievement in Pancasila education learning and citizenship for students of class X MIPA 2 State Senior High School 1 Sepauk in the 2021/2022 academic year. This research uses quantitative methods with the form of interactiberelationship study research. The sample in this study were students of class X MIPA 2 State Senior High School 1 Sepauk totaling 30 students. Tehciques and data collection tools using questionnaires and documentation. Hypothesis testing includes normality test,simple regression analysis, correlation analysis, and t test. The research data wa obtained from the resukts of a questionnaire on learning interest and student achievement from the academic report cards for the odd semester 2021/2022. Based on the calcution of the product moment correlation test, it is known that the correlation value is 0,776 that the interval coefficient is 0,60-0,779 and level og the relationship is relatively strong. Based on te t-test it is known that tcount is 0,851 and t-table = n-2 =30-2 is 28 t-table =0,374, so 0,851 > 0,374 Ha is accepted. So it can be said that there is a significant correlation between interest and learning achievement in Pancasila education learning and citizenship for students of class X MIPA 2 State Senior High School 1 Sepauk in the 2021/2022 academic year. Keywords: Interest, and Student Achievement